2021
DOI: 10.3892/etm.2021.10514
|View full text |Cite
|
Sign up to set email alerts
|

Thickening of the walls of deep brain abscesses is associated with macrophage infiltration

Abstract: The present study aimed to compare the thickness of brain abscesses in the deep and the superficial brain and to investigate the factors that influence the capsule of brain abscesses. The thickness of the brain abscess wall was evaluated on imaging. Bacteriological examination was performed on the abscess pus and wall, and immunohistochemical staining was used to count the number of macrophages. Kaplan-Meier curves were used to analyze overall survival. The results indicated that the wall of deep-brain abscess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…For example, the quantitative results showed that the ratio of the F4/80 marker area in the MSN@DOX-AMP group was only 14.8% of that in the Blank group (Figure D and SI Figure S35), demonstrating that the level of macrophage infiltration decreased. It should be caused by the antimicrobial activity of AMP, as the bacterial infection would result in serious macrophage infiltration. , Additionally, MSN@DOX-AMP would not polarize the macrophage in vitro (SI Figure S36). CD3 expression indicates the level of infiltration of T lymphocytes, and this expression is positively correlated with the activity of specific antitumor immunity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the quantitative results showed that the ratio of the F4/80 marker area in the MSN@DOX-AMP group was only 14.8% of that in the Blank group (Figure D and SI Figure S35), demonstrating that the level of macrophage infiltration decreased. It should be caused by the antimicrobial activity of AMP, as the bacterial infection would result in serious macrophage infiltration. , Additionally, MSN@DOX-AMP would not polarize the macrophage in vitro (SI Figure S36). CD3 expression indicates the level of infiltration of T lymphocytes, and this expression is positively correlated with the activity of specific antitumor immunity .…”
Section: Resultsmentioning
confidence: 99%
“…It should be caused by the antimicrobial activity of AMP, as the bacterial infection would result in serious macrophage infiltration. 52,53 Additionally, MSN@ DOX-AMP would not polarize the macrophage in vitro (SI Figure S36). CD3 expression indicates the level of infiltration of T lymphocytes, and this expression is positively correlated with the activity of specific antitumor immunity.…”
Section: Modulation Of the Immunosuppressive Tumor Microenvironment I...mentioning
confidence: 99%
“…Brain abscess develops into a focal accumulation of pus from an initial localized area of infectious cerebritis with generally five concentric histological zones: a necrotic center; surrounded by a well vascularized capsule corresponding to peripheral inflammatory cells, macrophages, and fibroblasts; a dense collagenous capsule; a layer of neovascularization with cerebritis, and external astrogliosis and cerebral edema. A recent bacterial and immunohistochemical study pointed out that the wall of deep-brain abscesses was significantly thicker than that of superficial brain abscesses with a greater degree of macrophage infiltration [1].…”
Section: Pathogenesis and Epidemiologymentioning
confidence: 99%
“…Recent MRI studies suggest that perfusion (dynamic susceptibility contrast, DSC) may help discriminate brain abscesses from malignant lesions [1]. Low relative Cerebral Blood Flow (rCBV) is a good indicator of a brain abscess, whereas a tumor typically has higher rCBV, reflecting neoangiogenesis.…”
Section: Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation